KEPENTINGAN AMERIKA SERIKAT MEMPERKARAKAN BEA ANTI-DUMPING CHINA TERHADAP PRODUK OTOMOTIF KE WTO - Fajar Satria; Den Yealta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research describe about the interest of United State bringing China’s anti dumping duties into court on automotive product to World Trade Organization (WTO). China raised import duties on United State automotive product by up to 30%, which caused companies to feel disadvantage.   The study was prepared using the protection theory by Friedrich List, concept national interest, the Mercantilism perspective, which is then supported by nation-state analysis level. The methodology using a qualitative method and collecting the data using a library research literature.This research shows the united State’s bringing China anti-dumping duties into court is for national interest. That is to protect its automotive company to export automotive product from disadvantage. And to protect its credibility as one of the biggest country to exporting products.  Key Words: Protectionism, Anti-Dumping, Countervailing Duties, World Trade Organization, Dispute Settlement Body.